Apolipoprotein E Overexpression Is Associated With Tumor Progression and Poor Survival in Colorectal Cancer - Zhao, Zhixun; Zou, Shuangmei; Guan, Xu; Wang, Meng; Jiang, Zheng; Liu, Zheng; Li, Chunxiang; Lin, Huixin; Liu, Xiuyun; Yang, Runkun; Gao, Yibo; Wang, Xishan (Frontiers in Genetics, 2018)
Apolipoprotein E (ApoE) plays a key role in tumorigenesis and progression, such as cell proliferation, angiogenesis and metastasis. ApoE overexpression was associated with aggressive biological behaviors and poor prognosis in a variety of tumor according to previous studies. This study aimed to assess the prognostic value and explore the potential relationship with tumor progression in colorectal cancer (CRC). We collected the expression profiling microarray data from the Gene Expression Omnibus (GEO), investigated the ApoE expression pattern between the primary CRC and liver metastasis of CRC, and then explored the gene with prognostic significance based on the TCGA database. ApoE high expression was associated with poor overall survival (OS, p=0.015) and progression-free survival (PFS, p=0.004) based on the public databases. Next, ApoE expression was evaluated in two CRC cohorts by immunohistochemistry, of whom 306 cases were stage II and 201 cases were metastatic liver CRC. In the cohort of the liver metastasis, the ApoE expression was increasing in normal mucosa tissue, PCC and CLM in order. Meanwhile, the level of ApoE expression in stage II tumor sample which had no progression evidence in 5 years was lower than that in PCC of synchronous liver metastases. The high ApoE expression in PCC was an independent risk factor in both stage II (HR=2.023, [95% CI 1.297-3.154], p=0.002; HR=1.883, [95% CI 1.295-2.737], p=0.001; OS and PFS respectively) and simultaneous liver metastasis (HR=1.559, [95% CI 1.096-2.216], p=0.013; HR=1.541, [95% CI 1.129-2.104], p=0.006; OS and PFS respectively). However, the overexpression of ApoE could not predict the benefit from the chemotherapy in stage II. The study revealed that the relevance of the ApoE overexpression in CRC progression, conferring a poor prognosis in CRC patients especially for stage II and simultaneous liver metastasis. These finding may improve the prognostic stratification of patients for clinical strategy selection and promote CRC clinic outcomes.